2019
DOI: 10.1186/s40694-019-0075-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of PKAc1 in gene regulation and trichodimerol production in Trichoderma reesei

Abstract: Background Trichoderma reesei represents a model system for investigation of plant cell wall degradation and its connection to light response. The cyclic adenosine monophosphate pathway (cAMP pathway) plays an important role in both physiological outputs, being crucial for regulation of photoreceptor function as well as for cellulase regulation on different carbon sources. Phosphorylation of photoreceptors and of the carbon catabolite repressor CRE1 was shown in ascomycetes, indicating a releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 77 publications
(134 reference statements)
2
25
0
Order By: Relevance
“…5 ). This result is consistent with previous study that phosphorylation of Cre1 affects its nuclear import and export [ 30 ] and plays an important role in cellulase production in T. reesei [ 31 ]. Thus, we suggested that phosphorylation of the C-terminal of Cre1 plays an important role on its subcellular localization and has a direct relationship with CCR.…”
Section: Discussionsupporting
confidence: 94%
“…5 ). This result is consistent with previous study that phosphorylation of Cre1 affects its nuclear import and export [ 30 ] and plays an important role in cellulase production in T. reesei [ 31 ]. Thus, we suggested that phosphorylation of the C-terminal of Cre1 plays an important role on its subcellular localization and has a direct relationship with CCR.…”
Section: Discussionsupporting
confidence: 94%
“…Among the potential phosphorylation target sites in the region covering amino acids 387-390 at the C-terminus of Cre1, S388 maybe be phosphorylated by PKA, in contrast to S387, T389, and T390. As a conserved nutrient-sensing pathway, the cAMP-PKA pathway plays an important role in the response to environmental carbon availability to activate or repress the relevant downstream genetic pathways (Ortiz-Urquiza and Keyhani, 2015;Hinterdobler et al, 2019) . In Aspergillus fumigatus and Neurospora crassa, PKA is activated in the presence of glucose, thereby inhibiting alternative carbon source usage due to CCR (Brown et al, 2014;Huberman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…HPTLC analysis was done according to Hinterdobler et al (2019) with some modifications. Metabolites were extracted from the agar by supersonication for 15 min in a mixture of 5 ml water (p.A.)…”
Section: Methodsmentioning
confidence: 99%